The Heat of Combustion of Beryllium in Fluorine - Churney, K. L (J Res Natl Bur Stand A Phys Chem, 1969)
An experimental determination of the energies of combustion in fluorine of polytetrafluoroethylene film and powder and of mixtures of beryllium with polytetrafluoroethylene gives for reaction (1) [Formula: see text] kJ mol(−1) (−244.32 kcal mol(−1)) with an overall precision of 0.96 kJ mol(−1) (0.23 kcal mol(−1)) at the 95 percent confidence limits. The total uncertainty is estimated not to exceed ±3.2 kJ mol(−1) (±0.8 kcal mol(−1)). The measurements on polytetrarluoroethylene give for reaction (2a) and reaction (2b) [Formula: see text] and −10392.4 Jg(−1), respectively. Overall precisions expressed at the 95 percent confidence limits are 3.3 and 6.0 Jg(−1), respectively. (1). [Formula: see text] (2a). [Formula: see text] (2b). [Formula: see text] Be(2)C and Be metal were observed in a small carbonaceous residue from the combustion of the beryllium-polytetrafluoroethylene mixtures. Methods of analysis for these substances were developed. Gases resulting from the solution of the solid residues in aqueous KOH were analyzed for H(2) and CH(4) by differential absorption in molecular sieves at low temperatures.